Healing the Mind and Soul an Islamic Approach to Mental Health and Resilience - Bukhari, Dr. Syed Hamid Farooq (Al Khadim Research Journal of Islamic Culture and Civilization, 2025)
The growing global awareness of mental health has highlighted the need for holistic approaches that consider not only psychological but also spiritual well-being. In Islamic tradition, the human being is viewed as a composite of body, mind, and soul, and true healing requires nurturing all three. This article explores the concept of mental health and spiritual resilience through an Islamic lens, emphasizing the role of faith, worship, and divine connection in fostering emotional stability and inner peace. The Qur’an and Sunnah acknowledge emotional challenges such as grief, fear, and anxiety, offering spiritual tools like sabr (patience), tawakkul (trust in Allah), dhikr (remembrance of God), and du‘ā (supplication) as means to cope. The life of the Prophet Muhammad ﷺ serves as a model of resilience amidst adversity, illustrating how spiritual strength can guide individuals through psychological distress. Historically, Muslim scholars like Al-Ghazali and Ibn Sina addressed mental and emotional disorders, proposing treatments rooted in both spiritual and rational practices. In modern contexts, integrating Islamic principles with evidence-based therapeutic methods can enhance mental health outcomes, especially for practicing Muslims. Spiritually integrated psychotherapy, Islamic mindfulness, and community-based support within the Ummah are crucial in this regard. This article also highlights the importance of removing the stigma around mental illness in Muslim communities and the proactive role mosques and scholars can play in this domain. Ultimately, Islam not only validates emotional struggles but offers a deeply rooted spiritual path to healing and resilience, promoting holistic well-being for the mind and soul.